A figura e forma da terra no pensamento geográfico ocidental: da antiguidade clássica ao debate cartesiano/newtoniano (séculos XVII-XVIII) - Maguenillski, Diego (2021)
The present study seeks through a long bibliographical research to plain and address the main cosmographic conceptions and estimates about the shape of the planet Earth, our home, in the history of Western geographic thought. To this objective, we defined a temporal cut that comes from the first Written Greek records, around the 8th century B.C., until the mideighteenth century, when the contributions of Isaac Newton (1643-1727) about the shape of the Earth were tested in the field, in the geographical expeditions of French academics, in 1735 and 1736. Our study serves of a broad bibliographic repertoire (books, articles, theses, dissertations, web pages) to be able to discuss the characteristics of geographic thinking in different moments in the history of the West: we count on the contributions of researchers of the history and epistemology of Science such as Boorstin (1989), Dreyer-Eimbcke (1992), Kimble (2005), Bauab (2012), Santos (2002), Brotton (2014), Rossi (2001), Koyré (2001), Kuhn (2017), Carvalho (2006), among others. We have adopted the consultation of several original works of authors to better analyze their conceptions of the shape of the Earth and establish links with the geographical thought of their time. We have written three chapters, notably one on the Ancient Age (VIII BC – IV A.D.), other about the Middle Ages (V-XV A.D.), and other about the Modern Age (XV-XVIII). In the Ancient Age we have limited at the cosmographic conceptions and estimates about the shape of the Earth of Roman and Greek civilizations; in the Middle Age, we have studied the Christian cosmographic conceptions and the changes of Western Sciences, in the Europe. In our investigations at the Third Chapter, about the Modernity, we dedicate for the changes in the geographical conceptions of West, and for the revelation of the globality of the world, at the start of maritime discovery ventures, in the XV and XVI centuries; also, we discussed about the complex concept of Discovery in the considerations of Bornheim (1998) and Subirats (1998), and others; and we’ve addressed about the formation of modern European sciences, and the most important theoretic physical-cosmologic changes, when the Earth becomes considered a planet. For end, we’ve addressed about the French expeditions for Lapland and South América, in geodesic missions at the XVIII century, in the context of Cassinian-Cartesian/ Newtonian debate about the shape of planet, and your conclusions.